The protection of purchasers of immovable property in South Africa, with special reference to section 29a of the alienation of land act 68 of 1981 and the housing consumers protection measures act 95 of 1998 - Marais, Michele (Centre for Law and Society, 2026)
Ownership of land has occupied a special position in our legal history. lt has been said that "[t]the desire of individuals and social and political groups for the ownership of land is probably one of the greatest drives in human history. In non-industrial forms of society, the main source of a community's wealth is land. He who holds land [...] holds economic power, and ownership of-land becomes the basis of political power. The immovable and indestructible nature of land has led to the view that it constitutes the best form of security. These qualities set larid apart from other commodities and make its ownership more complicated than the ownership of movables."¹